E-Module Of Cube And Cuboid Based On Ethnomathematics For Five-Grade Elementary School Students - Triwahyuningtyas, Dyah; Mahmuda, Novia Eka; Ardila, Ardila (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
The background of this research is to produce and develop cube and cuboid material e-module products centred on regional culture. The teaching materials are still printed books containing material and questions without any complex mathematical concepts, so there is a lack of linking regional culture with mathematics. That affects the lack of understanding of students' ethnomathematics during the geometry material pandemic. This study aims to develop an e-module cube and cuboid based on ethnomathematics for fifth-grade elementary school students. Research development methods with 4D include definition, design, development and deployment. The data was analyzed using quantitative and qualitative data analysis techniques through media and material expert validators and teacher and student response questionnaires. The results showed that the e-module cube and cuboid based on ethnomathematics were declared feasible or valid with an average score of 82.5%. They used e-modules through teacher and student response questionnaires and obtained an average score of 85%, which was stated to be very practical. Therefore, it affects students' cognitive understanding of cube and cuboid material with an average value of 84.1. The ethnomathematics-based e-module cube and cuboid can help students improve their contextual abilities.